2023
DOI: 10.1021/jacs.3c00563
|View full text |Cite
|
Sign up to set email alerts
|

Remote-Triggered Domino-like Cyclodehydrogenation in Second-Layer Topological Graphene Nanoribbons

Abstract: Cyclodehydrogenation reactions in the on-surface synthesis of graphene nanoribbons (GNRs) usually involve a series of C sp2 −C sp2 and/or C sp2 −C sp3 couplings and just happen on uncovered metal or metal oxide surfaces. It is still a big challenge to extend the growth of second-layer GNRs in the absence of necessary catalytic sites. Here, we demonstrate the direct growth of topologically nontrivial GNRs via multistep C sp2 −C sp2 and C sp2 − C sp3 couplings in the second layer by annealing designed bowtie-sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…However, the strong charge transfer between the GNRs and metallic substrates may quench the local spins. 133,134 Recent progress has demonstrated that the direct growth of second-layer GNRs, by utilizing the remote-triggered domino-like effect in the cyclodehydrogenation reactions, resulted in quasi-freestanding topological spin states with strong enough screening from the metallic substrate to induce Kondo resonance 124 (Figure 4b). By further exploration under high magnetic fields, a Landéfactor g = 2.7 ± 0.5 was obtained for the quasifreestanding topological end spins.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the strong charge transfer between the GNRs and metallic substrates may quench the local spins. 133,134 Recent progress has demonstrated that the direct growth of second-layer GNRs, by utilizing the remote-triggered domino-like effect in the cyclodehydrogenation reactions, resulted in quasi-freestanding topological spin states with strong enough screening from the metallic substrate to induce Kondo resonance 124 (Figure 4b). By further exploration under high magnetic fields, a Landéfactor g = 2.7 ± 0.5 was obtained for the quasifreestanding topological end spins.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
“…(b) Directly synthesizing second-layer GNRs with designer topological states that host quantum spins. Reprinted in part with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…C aryl –C aryl coupling is at the core of on-surface synthesis toward the precise fabrication of low-dimensional covalent nanostructures, as represented by the pioneering works on covalent on-surface polymerization . Over the past 16 years, numerous organic reactions from conventional solution chemistry have been transferred to metal surfaces (typically coinage metals) under ultrahigh vacuum conditions. Among them, there are two kinds of most popular on-surface reactions for C aryl –C aryl bond formation, namely dehydrogenative C aryl –C aryl coupling and dehalogenative C aryl –C aryl coupling, which have been applied to the on-surface synthesis of various nanographene molecules, graphene nanoribbons, and other carbon allotropes beyond graphene. , These carbon-based materials hold great promise for future organic electronics. , Building covalent nanostructures with atomic precision is crucial to achieving desired electronic properties, which requires reliable control over the C aryl –C aryl coupling process.…”
Section: Introductionmentioning
confidence: 99%